Role of public administration in promoting sociopolitical development - De Leon, Corazon Alma G. (1998)
Public administration plays an intricate role in promoting sociopolitical development. At the center of the exposition is the argument that good public administration or governance is a necessary ingredient for development. As the Philippine seeks to achieve a high level of sociopolitical development, the Philippine civil service should therefore be reformed to further enhance its capability in advancing sociopolitical goals.
Keywords: Civil Service Commission; Deregulation; Governance; Public administration